Update - Ocean Power Catches a Wave. - Jones, W.D.
Three snakelike wave-power generators built by Edinburgh's Pelamis Wave Power delivers 2.25 megawatts through an undersea cable to the Portuguese coastal town of Agucadoura. Within a year, another 28 generators should come online there, boosting the capacity to 22.5 MW. That may be a trickle of power, but the project represents a new push into wave and tidal power as governments eye the oceans as a way to meet their renewable energy targets.
Keywords: Power 2.25 MW; Power 22.5 MW; Renewable energy; Tidal power; Undersea cable; Wave power; Wave-power generators